Immobilization of Thermomyces lanuginosus lipase on multi-walled carbon nanotubes and its application in the hydrolysis of fish oil. (8th December 2017) - Matuoog, Naeema; Li, Kai; Yan, Yunjun
Abstract: In this study, lipase from Thermomyces lanuginosus (TLL) was immobilized on carbon nanotubes (MWCNTs) by physical adsorption, and the immobilizing conditions were optimized for maximum activity. The effects of enzyme loading, pH, temperature and time on the immobilization efficiency and specific activity were evaluated. The highest enzyme activity and immobilization efficiency of 90.66% and 110.5%, respectively, were achieved when the immobilized pH was 8, and a high rate of recovery activity of 111.3% occurred at 45 °C with 30–60 min providing a good result. When the immobilization efficiency was 95.8%, the recovery activity was 112.4%. The immobilization time had little effect on the immobilization efficiency, and 6 mg g −1 of lipase provided the highest immobilization efficiency of 97.78% and recovery activity of 112.8%. When the immobilized lipase was utilized to enrich docosahexaenoic acid (DHA) from fish oil, the DHA content increased with increasing amount of lipase up to 9 mg g −1 . The water content had a clear effect when of 50% water was used at 45 °C and at a pH of 7 after 10 h. The DHA contents were 4.2-fold and 2.5-fold greater than the initial content of DHA fish oil for TLL-MWCNTs and free lipase, respectively. The degrees of hydrolysis after 6 cycles of successive use were over 80% and 62% for the immobilized TLL and free TLL, respectively, indicating the system recyclability and the ease of use of the immobilized TLL in industrial applications, especially in the fields of food and medicine.